Mechanical and surface properties of additive manufactured zirconia under the different building directions - Miura Shoko; Shinya Akikazu; Ishida Yoshiki; Fujisawa Masanori (JAPAN PROSTHODONTIC SOC, 2025)
Purpose: This study investigates the mechanical and surface properties of zirconia manufactured using additive manufacturing (AM) technology and the effect of the building direction on the mechanical and surface properties.
Methods: Specimens were prepared using ZrO2 paste (3DMix ZrO2; 3DCeram) and a three-dimensional printing system (CeraMaker 900; 3DCeram) based on the principles of stereolithography (SLA). The mechanical properties (flexural strength, Vickers hardness, fracture toughness, elastic modulus, and Poisson's ratio) and surface properties (chemical composition and surface observation) were evaluated for three building directions (parallel, diagonal, and perpendicular) to investigate the relationship between the building directions and the anisotropy of the mechanical and surface properties of SLA-manufactured zirconia. Statistical analysis was performed using a one-way analysis of variance and Tukey's honestly significant difference test.
Results: The highest flexural strength was obtained for a perpendicular building direction. The flexural strength was significantly higher in the perpendicular direction than in the parallel and diagonal directions; it was also significantly higher in the diagonal direction than in the parallel direction (p<0.05). The Vickers hardness, fracture toughness, elastic modulus, Poisson's ratio, and chemical composition did not differ significantly. Microstructural observations revealed that the layers, large crystals, and pores were more prominent in the parallel direction.
Conclusions: The flexural strength and surface structure of the tested SLA-manufactured zirconia were influenced by the building direction; however, other mechanical properties remained unaffected. The layer boundaries affected the anisotropic behavior of the builds to a certain extent, owing to the layer-by-layer production method.